Influence of Servicecape and Brand Experience on Customer Satisfaction Café the Main Show of Chicken Noodles & Coffee In Medan City - Adita Wanda Syahputri Siregar; Endang Sulistya Rini; Beby Karina Fauzeea Sembiring (Budapest International Research and Critics University, 2022)
Customer Satisfaction is the main goal of large or small companies today. In general, consumers want to enjoy a cafe that suits their needs and desires such as the suitability of music, cafe atmosphere, temperature, lighting, and others. On the other hand, the company must also be able to anticipate when the number of visitors is booming with the employees provided in order to adjust the needs and desires of consumers. The results of the pre survey found that the majority of respondents did not have good knowledge about Café Sinar Utama Mie Ayam & Kopi, as well as servicecape, the majority of respondents did not think it was something important. This study aims to analyze the effect of Servicecape and Brand Experience on Customer Satisfaction at Cafe Sinar Utama Mie Ayam & Kopi in Medan City. The population in this study were all consumers who visited or came to the Sinar Utama Mie Ayam & Kopi cafe in the city of Medan whose number was unknown. While the samples taken in this study were 96 respondents. Data collection by distributing questionnaires. This research is field research (field research) using quantitative methods with multiple linear regression analysis which is processed in the SmartPls version 3.0 application. The results of the study indicate that Servicecape and Brand Experience have a positive and significant impact on Customer Satisfaction at Cafe Sinar Utama Mie Ayam & Kopi Medan. Based on the F-Square test, it shows that Servicecape has a moderate or moderate influence on Customer Satisfaction while Brand Experience has a substantial or strong influence on Customer Satisfaction. Therefore, the main light cafe, Mie Ayam & Kopi Medan, needs to evaluate the Servicecape so that it can affect Customer Satisfaction more effectively and efficiently.